Information Overload in Patient Education: A Wilsonian Concept Analysis. (July 2022) - Wang, Tongyao; Voss, Joachim G.
The authors of this concept analysis seek to clarify the concept of information overload within the context of patient education in healthcare. A modified six-step Wilsonian concept analysis method with a review of qualified manuscripts from PubMed, PsycInfo, CINAHL, and MEDLINE from 2000 to 2018 was conducted. Information overload occurs when an individual acknowledges that information received is beyond his or her information-absorbing threshold. The causes include quantity and quality of the information and information delivery structures. Information overload is associated with higher levels of stress and poor self-care performance. It is significant for healthcare providers to recognize patients' feelings of information overload.